Proliferation of Interstitial Cells in the Cyclophosphamide-Induced Cystitis and the Preventive Effect of Imatinib. (18th June 2017) - Sancho, Maria; Triguero, Domingo; Lafuente-Sanchis, Aranzazu; Garcia-Pascual, Angeles
Abstract : Cyclophosphamide- (CYP-) induced cystitis in the rat is a well-known model of bladder inflammation that leads to an overactive bladder, a process that appears to involve enhanced nitric oxide (NO) production. We investigated the changes in the number and distribution of interstitial cells (ICs) and in the expression of endothelial NO synthase (eNOS) in the bladder and urethra of rats subjected to either intermediate or chronic CYP treatment. Pronounced hyperplasia and hypertrophy of ICs were evident within the lamina propria and in the muscle layer. IC immunolabeling with CD34, PDGFR α, and vimentin was enhanced, as reflected by higher colocalization indexes of the distinct pairs of markers. Moreover, de novo expression of eNOS was evident in vimentin and CD34 positive ICs. Pretreatment with the receptor tyrosine kinase inhibitor Imatinib prevented eNOS expression and ICs proliferation, as well as the increased voiding frequency and urinary tract weight provoked by CYP. As similar results were obtained in the urethra, urethritis may contribute to the uropathology of CYP-induced cystitis.